Regulation of Garcinol on Histone Acetylation in the Amygdala and on the Reconsolidation of a Cocaine-Associated Memory - Monsey, Melissa S.; Ruiz, Sonia G.; Taylor, Jane R. (Frontiers in Behavioral Neuroscience, 2020)
Exposure to environmental cues associated with drug taking often disrupts abstinence from cocaine use by triggering memories of drug effects, leading to craving and possible relapse. One prospective method of treatment is weakening cocaine-associated memories via impairment of memory reconsolidation. Previous experiments have shown that systemic injection of the amnestic agent garcinol impairs the reconsolidation of cocaine-cue memories in a temporally constrained, cue-specific, and long-lasting manner. Here, we investigated garcinol’s effect on cocaine-cue memory reconsolidation when administered to the lateral nucleus of the amygdala (LA), as well as its epigenetic activity following systemic garcinol administration and also when given in conjunction with TSA, a histone deacetylase (HDAC) inhibitor. Rats underwent 12 days of cocaine self-administration training where active lever presses resulted in an i.v. infusion of cocaine paired with a light/tone cue. After 8 days of lever extinction, rats received a memory reactivation session followed by a cue-induced reinstatement test. Intra-LA garcinol following memory retrieval significantly impaired reconsolidation only if the memory was reactivated. Additional studies revealed a significant site-specific reduction in histone H3 acetylation and reduced expression of the immediate-early genes Arc and Egr-1 in the LA. When administered alone, TSA enhanced the reinstatement of a cocaine-cue memory; an effect that was prevented when garcinol was concurrently administered. These data indicate the LA is a key structure responsive to garcinol, suggest that one of garcinol’s mechanisms of action is through the reduction of memory-related gene expression in the LA, implicate changes in histone acetylation in memory reconsolidation, and support garcinol as a potential therapeutic tool for sustaining abstinence.